Blog Influence on Purchase Intention of Beauty and Cosmetics Products : The Psychological Antecedents - W.H., Cheng; Y.N., Goh; N.N, Zainal; Janifer, Lunyai (MAJCAFE is a publication of Malaysian Consumer and Family Economics (MACFEA), 2022)
This study investigates the psychological antecedents on consumer purchase intention of beauty and cosmetic products. The psychological antecedents include advertising intent, experience goods, brand awareness, perceived credibility, and perceived usefulness. Meanwhile, attitude is posited to mediate the relationships between psychological antecedents and consumer purchase intention. This study was quantitative, utilizing of cross-sectional design, in which the data were gathered through a survey. This study focused on the consumers of beauty and cosmetic products in Malaysia. A structured self-administered survey involving 175 participants was conducted. PLS-SEM was used to analyse the collected data. Statistical tools, IBM SPSS Statistics Version 23.0 and Smart PLS version 3, were used for data analysis and hypothesis testing. The results showed that advertising intent, brand awareness, perceived credibility, and perceived usefulness are related to purchase intention. Surprisingly, experience goods did not have any influence on purchase intention. Also, attitude towards sponsored recommendation posts did not mediate the relationship between experience goods and purchase intention. Nevertheless, this study sheds some light on the values– attitude-behaviour hierarchy on purchase intention.